2018
DOI: 10.1016/j.athoracsur.2017.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Preferences Regarding Public Reporting of Outcomes in Congenital Heart Surgery

Abstract: Parents of children with congenital heart disease identify survival statistics, surgeon-specific experience, and complication rates as the most important outcome measures to report publicly. Additionally, parents preferred mortality data to be presented in a procedure-specific format using a numeric procedure-based approach, as opposed to the star rating system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…They are generally the most important metric to patients and currently the most widely used type of quality measures [1, 4]. Their use can be limited, however, when the event rate is low or when sample sizes are small [5].…”
Section: Donabedian’s Triadmentioning
confidence: 99%
See 2 more Smart Citations
“…They are generally the most important metric to patients and currently the most widely used type of quality measures [1, 4]. Their use can be limited, however, when the event rate is low or when sample sizes are small [5].…”
Section: Donabedian’s Triadmentioning
confidence: 99%
“…Recent studies suggest that up to 30% of patients can experience major complications after congenital heart surgery [18]. Parents, providers, and other stakeholders are interested in a child not only surviving surgery but thriving once the child is discharged home free of major morbidities [4]. From a health system and policy perspective, children with major morbidities are also more likely to consume greater health care resources [19].…”
Section: Quality Measurement In Congenital Heart Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Dr Irons and colleagues [1] are to be congratulated for their important analysis "Parent preferences regarding public reporting of outcomes in congenital heart surgery." The authors state: "Presented with three display formats for mortality rates, most (89%) identified a numeric procedure-based approach as the best format, and over half identified the hospital star rating system as the worst format."…”
Section: Variation In Outcomes Across Providers Has Beenmentioning
confidence: 99%
“…Importantly, the analysis by Irons and colleagues [1] does demonstrate that parents desire reporting of outcomes of individual operations, and that parents desire reporting of mortality, and of additional outcome metrics as well. The STS currently reports outcomes based on groupings of operative procedures stratified by the STAT Mortality Categories because of the relatively small numbers in which most individual pediatric cardiac surgical procedures are performed at individual institutions within any given time period.…”
Section: Variation In Outcomes Across Providers Has Beenmentioning
confidence: 99%